2017
DOI: 10.1111/fwb.12937
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional responses of leaf‐associated fungal communities to chemical pollution in streams

Abstract: resistance as well as the ability of these fungal communities to recover from pollution was 10 also assessed through a translocation experiment. with a shift in fungal structure after stress exposure, and ii) a recovery ability in terms of 20 laccase activity and fungal community structure two weeks after stress removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This kind of approach could thus be viewed as a powerful tool for developing predictive functional ecotoxicology in the sediment compartment, by considering the ecological role of both microorganisms and benthic invertebrates as consumers of organic matter. Reaching further forward, it should be possible to dissociate microbial-driven decomposition from invertebrate feeding, for example by enclosing the tablets in small-mesh-size bags (barring access to invertebrates) and large-mesh-size bags (giving access to invertebrates), as frequently used in studies assessing leaf-litter breakdown (Brosed et al, 2016;Rossi et al, 2017Rossi et al, , 2019. Finally, the methods tested here could be proposed for standardization to further improve sediment ERA protocol, as already done in the soil compartment through the TRIAD approach (ISO 19204, 2017).…”
Section: How Can Artificial Organic Matter Substrates Improve the Ecological Relevance Of Sediment Environmental Risk Assessment?mentioning
confidence: 99%
“…This kind of approach could thus be viewed as a powerful tool for developing predictive functional ecotoxicology in the sediment compartment, by considering the ecological role of both microorganisms and benthic invertebrates as consumers of organic matter. Reaching further forward, it should be possible to dissociate microbial-driven decomposition from invertebrate feeding, for example by enclosing the tablets in small-mesh-size bags (barring access to invertebrates) and large-mesh-size bags (giving access to invertebrates), as frequently used in studies assessing leaf-litter breakdown (Brosed et al, 2016;Rossi et al, 2017Rossi et al, , 2019. Finally, the methods tested here could be proposed for standardization to further improve sediment ERA protocol, as already done in the soil compartment through the TRIAD approach (ISO 19204, 2017).…”
Section: How Can Artificial Organic Matter Substrates Improve the Ecological Relevance Of Sediment Environmental Risk Assessment?mentioning
confidence: 99%
“…Fernández et al (2015) found a correlation between structural changes in microbial communities as well as fungal biomass with increasing predicted fungicide toxicity based on the chemical analysis and toxic unit calculation by combining fungicide monitoring with field studies on fungal communities. Rossi et al (2017) found differences in fungi community structure between alder leaves exposed in a pristine part of a stream and those exposed at a downstream site where several fungicides were detected by chemical analysis. Gardeström et al (2016) observed that fungal communities from an agriculturally influenced stream were more tolerant to azoxystrobin than a community without a history of pesticide exposure, indicating a shift in community composition toward tolerant species, also known as pollution induced community tolerance (Molander et al, 1990).…”
Section: Exposure and Effects Of Fungicides On Freshwater Fungimentioning
confidence: 85%